Importance-Performance Analysis of Online Insurance: Communication and Networking - Ming-Hsi Tang; Yu-Lin Niu (Engineering Proceedings, 2023)
Over the past few decades, drastic advances in technology have forced insurers to seek transformation in order to survive in a changing environment. Along with the outbreak of COVID-19, online insurance has become a much-needed distribution channel for insurers, not only as a cost-effective option, but also in line with pandemic prevention measures. However, in contrast to insurers’ vast investment in AI, chatbots, etc., online insurance only accounted for less than 2% of the total premium in Taiwan in 2022. This article uses importance-performance analysis (IPA) to identify disparities between client perceptions of crucial elements of online insurance services and their actual performance. The results show that among constructs such as perceived usefulness, ease of use, security, and service quality, customer experience can be greatly enhanced if insurers prioritize improving website security and service quality.